A Historical Overview, Analysis, and Wind Transcription of Frank Zappa's "Sad Jane" - Nguyen, Vu (My University, 2013)
This dissertation explores a selection of orchestral works by American composer Frank Zappa (1940-1993), focusing on those recorded by Kent Nagano (b. 1951) and the London Symphony Orchestra (LSO) in 1983. Chapter 1 offers a biographical snapshot of Zappa, including events and factors, such as his autodidactic musical education, that contributed to his musical development and eclectic musical tastes that straddle the worlds of pop and art music. Chapter 2 explores the relationship between Zappa and the various performers he worked with on productions of his large orchestral pieces. This includes his professional relationship with Nagano, his interactions with the musicians of the LSO and Berkeley Symphony Orchestra, as well as the dancers and choreographers involved with A Zappa Affair. Chapter 3 provides an analysis of "Sad Jane" and a discussion about the author's transcription of it for wind ensemble.
Thesis (D.M.A.)--University of Washington, 2012
Keywords: A Zappa Affair; London Symphony Orchestra; Nagano; Sad Jane; Wind Ensemble; Zappa; Music; music